Regularity and mechanisms of water-sand inrushes within mining-activated faults - Shichuan ZHANG; Pu HUANG; Yangyang LI; Chenggong WANG; Zhenhua WU (Meitian dizhi yu kantan)
BackgroundDuring underground coal mining, water-sand mixtures within faults may rush into mine floors. The water-sand inrushes are especially prominent under the conditions of high water-yield properties and loose filling structures in fault zones, severely threatening the safe mining of coal mines. Previous studies focus primarily on the impact of a single factor on inrushes. Hence, it is significant to systematical investigate the regularity of water-sand inrushes within faults under the combined effects of multiple factors. MethodsBased on the fluid and granular mechanic theories, this study derived the instability criterion and flow formulas of water-sand mixtures. Using orthogonal experiments on three factors at four levels, along with a deformations-seepage test system for fractured rocks, this study investigated the impacts of clay mass fraction, sand-grain size, and initial water pressure on the inrush behavior. Results and Conclusions Clay significantly inhibited the inrush behavior. Under a clay mass fraction of 40%, the inrush behavior exhibited extremely low flow and load. The initial water pressure served as the primary force driving the inrush behavior. An increase in initial water pressure significantly enhanced the inrush intensity. The sand grain size manifested a nonlinearly regulating effect on the inrush behavior. Small or large sand grain sizes were prone to cause system instability, while moderate grain sizes could balance permeability and system stability. The multivariate statistical analysis reveals that the impacts of various factors on the inrush behavior decreased in the order of clay content, initial water pressure, and sand-grain size. The predicted optimal test conditions to minimize the flow, load, and pore water pressure include a clay mass fraction of 30%, an initial water pressure of 0.3 MPa, and sand grain size ranges of [0.3, 0.5] mm, [1, 2] mm, and [0.5, 1.0) mm, respectively. The results of this study will provide a theoretical basis for the prevention and control of water-sand inrushes caused by mining-induced fault activation.